The Effectiveness of Using Quizizz in Numerational Literacy Skills of Fractional Materials in 3rd Grade Students of Elementary School - Rara Andyra; Kowiyah Kowiyah (Jurnal Cendekia : Jurnal Pendidikan Matematika, 2022)
The purpose of its application in this study is to determine the effectiveness of using Quizizz game-based application media in numeracy literacy skills. The method implemented in this research is a combination method with Explanatory Sequential Designs. The data collection technique used is a matter of numeracy literacy test material assisted by Quizizz, e-questionnaire assisted by google form, and interview sheet. The subjects used were 25 students of class III C Ibnu Batutah SD IT Harum for the 2021/2022 academic year. The results of data processing, the average value obtained by students with Quizizz media on all indicators is 81.80 with a percentage of 80% of students belonging to the complete group, compared to the average value obtained by students who only use paper, which is 68.80 with a percentage of 40% of students belonging to the complete group. In further testing using SPSS version 25 through the paired sample t-test the value of sig (2-tailed) is smaller than 0.05, namely 0.000 < 0.05, meaning is rejected and is accepted. The results of the open questionnaire and interview process showed that all students gave positive responses in using the Quizizz application media when working on questions. This study concludes that there is an influence in the use of Quizizz application media in numeracy literacy skills in third third gradients of SD IT Harum.